2008
DOI: 10.4319/lo.2008.53.3.1076
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen loss rates during aging of lake sediment: Changes over 27 years studied in varved lake sediment

Abstract: We used a collection of ten freeze cores of annually laminated (varved) lake sediment from Nylandssjö n in northern Sweden collected from 1979 to 2007 to follow the long-term loss of carbon (C) and nitrogen (N) due to processes that occur in the lake bottom as sediment ages. We compared specific years in the different cores. For example, the loss of C from the surface varve of the 1979 core (sediment deposited during 1978) was followed in the cores from 1980, 1985, 1989, and so on until 2006. The C concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(155 citation statements)
references
References 28 publications
9
145
1
Order By: Relevance
“…Third, small differences between samples can also be introduced during subsampling, handling, and analyses. Nevertheless, previous studies have shown very good reproducibility for total C and N concentrations between cores (Gä lman et al 2006). This is in agreement with recorded trends in Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Third, small differences between samples can also be introduced during subsampling, handling, and analyses. Nevertheless, previous studies have shown very good reproducibility for total C and N concentrations between cores (Gä lman et al 2006). This is in agreement with recorded trends in Fig.…”
Section: Discussionsupporting
confidence: 81%
“…However, these experiments also indicate that diagenesis was effectively complete after only 25 days. Moreover, an analysis of varved sediments over time has revealed that as much as 20 % of organic C and as much as 30 % of organic N can be lost in situ from lake sediments, but that most of this loss occurs in the first 5 yr following deposition (Gälman et al, 2008). Therefore incomplete diagenesis cannot fully explain the increases in organic C and N that are observed over 100 to 200 yr in these alpine lakes.…”
Section: Implications For Biogeochemistrymentioning
confidence: 92%
“…Accordingly, marine and terrestrial OM is characterized by molar C/N ratios of 20 4-10 and > 20, respectively. However, C/N of OM produced in the euphotic zone is potentially elevated during sinking (Müller, 1977;Meyers, 2003) and diagenesis (Gälman et al, 2008) due to preferential degradation of N over C. Conversely, adsorption of ammonia (produced upon OM decomposition) on to clay mineral surfaces has the potential to decrease sediment C/N during diagenesis especially in sediments with less than 0.3 % of Corg (Müller, 1977). Despite these potential constraints, C/N ratio often accurately records past variations in the source of OM to the seafloor (Meyers, 1994;1997), as suggested for the coastal 25…”
Section: Carbon To Nitrogen Ratiomentioning
confidence: 99%